Stabilization of the TAK1 adaptor proteins TAB2 and TAB3 is critical for optimal NF‐κB activation. (29th January 2020) - Braun, Harald; Staal, Jens
Abstract : TAB2 and TAB3 bind to K63‐linked polyubiquitin chains and recruit the critical kinase MAP3K7 (TAK1). The polyubiquitin‐recruited TAK1/TAB2/TAB3 complex comes in close proximity with the IKK (IKKα/IKKβ/IKKγ) complex, which is recruited to M1‐linked polyubiquitin chains via the IKKγ (NEMO) component. Together, the two complexes activate the NF‐κB family of transcription factors. NF‐κB transcription factors are critical mediators of pro‐inflammatory signals and must be tightly regulated at multiple levels. Recently, it was discovered that one such point of regulation occurs at the level of TAB2 and TAB3 protein stability by the deubiquitinase USP15. Comment on: https://doi.org/10.1111/febs.15202 Abstract : Proposed model for the positive regulatory effects of USP15 on the activation of signaling pathways induced by TNF or IL‐1β by TAB2/3 stabilization. TNF or IL‐1β‐induced receptor activation leads to the recruitment and activation of the TAK1‐TAB2/3 complex, eventually inducing NF‐kB activation via the IKK complex. This is an invited commentary on the paper: USP15 potentiates NF‐κB activation by differentially stabilizing TAB2 and TAB3 (https://doi.org/10.1111/febs.15202 ). Comment on: https://doi.org/10.1111/febs.15202